Content Sources of Anti-Corruption Education in Russian Pedagogy - Grigory S. Bukharin (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Anti-corruption education prevents corruption, but its content remains understudied. The article traces the genesis and development of anti-corruption education as a scientific category in Russian pedagogy. The author applied standard research methods, as well as the systemic, dialectical, and historical methods, to Russian laws and works by Russian educators to describe the domestic anti-corruption education in IX–XXI centuries. The anti-corruption education has always relied on cultural and historical values, moral ideals, personal attitudes, individual civic and moral qualities, and anti-corruption behavior patterns. All these content elements were divided into axiological and activity components. The axiological component included moral and ethical norms, e.g., truth, justice, and civic consciousness. It also involved such personal qualities as law-abiding, honesty, unselfishness, discipline, diligence, responsibility, and duty. The activity component was represented by passive and active anti-corruption behavior patterns. The evolution of the content of anti-corruption education makes it possible to select the most effective forms and methods of educational impact.